2001
DOI: 10.2174/1381612013398491
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nitric Oxide in Gastrointestinal Inflammatory and Ulcerative Diseases: Perspective for Drugs Development

Abstract: Nitric oxide is a ubiquitous molecule involved in a variety of biological processes. The specific action of NO depends on its enzymatic sources namely neuronal nitric oxide synthase (nNOS), endothelial NOS (eNOS) and inducible NOS (iNOS) and all three isoforms have been localized in the gastrointestinal tract. Constitutive synthesis of NO by nNOS or eNOS isoforms is involved in the maintaining of the gastrointestinal mucosal integrity through modulation of gastric mucosal blood flow, epithelial secretion and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 109 publications
(136 reference statements)
4
37
0
2
Order By: Relevance
“…Also, other investigations have shown an increase in its levels in the colonic samples of animals with TNBS-induced colitis. Results of the TBARS assay in colonic tissue revealed that silymarin attenuates colonic damage by down-regulating the lipid peroxidation process, confirming previous findings on the anti-oxidant properties of silymarin [26,33]. It likely exerts this effect through its ability to antagonize free radical production and activity, and maintaining a balance between oxidants and anti-oxidants.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Also, other investigations have shown an increase in its levels in the colonic samples of animals with TNBS-induced colitis. Results of the TBARS assay in colonic tissue revealed that silymarin attenuates colonic damage by down-regulating the lipid peroxidation process, confirming previous findings on the anti-oxidant properties of silymarin [26,33]. It likely exerts this effect through its ability to antagonize free radical production and activity, and maintaining a balance between oxidants and anti-oxidants.…”
Section: Discussionsupporting
confidence: 85%
“…Many researches have shown that constitutive production of NO from endothelial NO synthase (eNOS) is advantageous in acute colitis, although chronic overproduction of NO from iNOS is associated with perpetuation of inflammatory process [32][33][34]. Furthermore, silymarin diminishes the release of proinflammatory cytokines like IL-1, IL-6, interferon (IFN)-γ and TNF-α from activated immune cells and consequently lessens activation of other immune cells following their release [27].…”
Section: Introductionmentioning
confidence: 99%
“…Large amounts of iNOS-induced NO have been identified in gastric tissue damage during inflammatory processes (34), and high levels of iNOS expression and activity have been related to severe inflammation in ulcerative mucosal cells (35). Studies have revealed that iNOS is usually induced under oxidative reactions, wherein high levels of NO reacts with the superoxide anion, thus causing peroxynitrite generation, tyrosine-mediated nitration, hydroxyl radical production, cellular toxicity and tissue lesions (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…A atividade do NO foi relatada em endotélio, cerebelo, nervos não adrenérgicos não colinérgicos (NANC), macrófagos, neutrófilos, rins, células epiteliais pulmonares, mucosa gastrintestinal e miocárdio 6,[25][26][27][28] . O NO também pode ser responsável pela vasodilatação presente na angiogênese fisiológica ou patológica, como no caso de tumores 29 .…”
Section: Funções Do óXido Nítricounclassified